How does digital government influence public policy compliance in public health emergencies? —A study based on mixed method - Huo, Rongmian; Liu, Feimin; Wu, Li (Frontiers in Psychology, 2025)
The evolution of digital government is reshaping the dynamics of government-citizen interactions, fostering new modes of engagement, co-creation, and participatory governance. This study explores the impact of digital government, administrative burdens, and violation costs on public policy compliance, with a focus on public health emergencies. In Study 1, a survey of 697 participants from regions with different levels of digital government (high, medium, and low) was conducted. The findings indicate that perceptions of the usefulness, ease of use, and transparency of digital government systems are significant predictors of policy compliance, mediated by the administrative burden experienced by citizens. Additionally, digital literacy was found to moderate the relationship between administrative burden and compliance, highlighting the role of digital skills in public policy compliance. In Study 2, an experimental survey with 312 participants examined how violation costs influence the impact of digital government on policy compliance. Results show that violation costs significantly moderate this relationship, aligning with the theoretical framework of loss aversion. The findings offer insights into the boundary conditions under which digital government initiatives can effectively enhance policy compliance in the context of public health emergency, contributing to the broader discourse on governance and public policy implementation in digital contexts.